Journey to Mars: A Biomedical Challenge. Perspective on future human space flight - Bizzarri, Mariano; Masiello, Maria Grazia; Guzzi, Rodolfo; Cucina, Alessandra (Organisms. Journal of Biological Sciences, 2017)
Manned space flight has been the greatest human and technological adventure of the past half-century. Putting people into places and situations unprecedented in history is stirred the imagination while the human experience was expanding and redefining. Yet, space exploration compels humans to confront a hostile environment of cosmic radiations, radical changes in the gravity and magnetic fields, as well as social isolation. Therefore, any space traveller is submitted to relevant health-related threats. In the twenty-first century, human space flight is poised to continue, but it will enjoy the ongoing developments in science and technology. It will become more networked, more global, and more oriented toward primary goals. A novel international human space flight policy could help achieve these objectives by clarifying the rationale, the ethics of acceptable risk, the role of remote presence, and the need for balance between funding and ambition to justify the risk of human lives. In order to address such a challenge, a preliminary careful survey of the available scientific data is mandatory to set forth adequate countermeasures. Envisaged solutions should provide a sound and technically feasible approach for counteracting microgravity and cosmic rays effects, which represent the main health risk for space crews. This objective must necessarily be sustained by national/international space agencies, which would coordinate their common efforts into a defined international spaceflight program.